Synanthropic rodents as possible reservoirs of shigatoxigenic Escherichia coli strains - Blanco Crivelli, Ximena; Rumi, María V.; Carfagnini, Julio C.; Degregorio, Osvaldo; Bentancor, Adriana (Frontiers in Cellular and Infection Microbiology, 2012)
Shigatoxigenic Escherichia coli (STEC) strains are worldwide zoonotic pathogen responsible for different cases of human disease including hemolytic uremic syndrome (HUS). Transmission of STEC to humans occurs through the consumption of food and water contaminated by faeces of carriers and by person-to-person contact. The objective of this study was two-fold: (1) to investigate whether synanthropic rodents are possible reservoirs of STEC in the urban area and (2) whether a particular genus out of synanthropic rodent is the principal carrier of STEC. One hundred and forty-five rodents were captured in Buenos Aires City. Screening for stx1/stx2 and rfbO157 was done by PCR from the confluence zone. STEC isolates were further characterized with biochemical tests by standard methods. Additional virulence factors (eae, ehxA, and saa) were also determined by PCR. Forty-one of the rodents were necropsied and sample of kidney and small and large intestine were taken for histopathological diagnosis. The samples sections were stained with hematoxylin-eosin, and observed by light microscopy to evaluate the systemic involvement of these species in natural infections. STEC was isolated from seven out of 27 suspect animals at screening. The following genotypes were found in the STEC strains: stx1/stx2/ehxA (1), stx2 (4), stx2/ehxA (1), stx2/ehxA/eae (1). Neither gross nor microscopic lesions compatible with those produced by Shiga toxin were observed in the studied organs of necropsied rodents. The bivariate analysis including the 145 rodent's data showed that the isolation of STEC is associated positively to Rattus genus. This synanthropic species may play a role in the transmissibility of the agent thus being a risk to the susceptible population. Their control should be included specifically in actions to dismiss the contamination of food and water by STEC in the urban area, as additional strategies for epidemiological control.